KINERJA KEUANGAN PERUSAHAAN DI SEKITAR PERISTIWA PENGUMUMAN ESOP DAN PENGARUHNYA PADA NILAI PERUSAHAAN - Mardiantari, Ni Putu Eka; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 13 No 2 (2015), 2015)
The purpose of this study to determine the company's financial performance before and after the announcement of the ESOP and the effect of differences in performance occurs on the value of the company. The study used secondary data in the form of financial statements 56 observations company announced ESOP samples selected with particular consideration (purposive sampling). Two different test average paired for the first hypothesis and simple regression analysis (t-test), which is preceded by the classical assumption for the second hypothesis with the help of Statistical Product and Service Solutions (SPSS) is a data analysis technique used. Conclusion The results of the research is the implementation of the ESOP in the company is able to improve the financial performance of companies that have an impact on the value of the company executive.
Keywords: esop, financial performance, company value